157 Control of methicillin-resistant staphylococcus aureus infections in two neonatal care units. (23rd September 2015) - Colomb, B; Bouthet, M f; Aho, S; Astruc, K; Guerre, G; Neuwirth, C; Henri, N; Amiot, S; Lévy, A; Gouyon, J B
Abstract : Context: Grouped cases of nosocomial bacterial infections (NBI) due to methicillin-resistant staphylococcus aureus (MRSA) were observed over a 1-year period (May 2007 to May 2008) in the neonatal intensive care unit and the unit of neonatology of a university hospital. Main purpose: To assess the implementation of preventive measures and the concomittant changes of the incidence of severe MRSA infections. Method: A head committee has been brought up on May 2008 (CLIN's president, head division of paediatrics, paediatricians and nurses of the neonatal units, chief nurses, hygienists, and bacteriologists). Two operational groups consisting of 15 persons each have been set up (one for each neonatal unit). Their aim was to provide information and formation to the care givers, and also to set up an internal audit of the care practices. The teams of the neonatal units were directly involved in the identification of at risk situations using a voluntary and anonymous declaration system. Over the May 2008–December 2008 period, the two operational groups performed the analysis of the results and suggested 90 actions that were validated by the head committee. Since May 2008, a direct observation of the practices of care has been started and the data have been stored in a computer software. This observation was performed by specifically trained nurses (two full-time employments). Meetings of the operational groups have been held monthly in order to evaluate changes in clinical practices (hand hygiene, central venous catheter insertion, etc…), analyse cases of NBI (definitions according to the CDC classification) and changes in nasal MRSA carriage rate (screening started in May 2008). In each neonatal unit, panels presented the conclusions of these meetings. An independent external audit of this method has been conducted in November 2008 by the Institut National de Veille Sanitaire (INVS) and the CCLIN Est. Results: Among 90 identified points of improvement, 82 (90%) actions have been implemented between May and December 2008. Hydro-alcoholic solution's consumption doubled from June 2008. Conformity rate for hand hygiene grew from 85% (July 2008) to 94% (December 2008) in the NICU, and from 38% to 95% in the unit of neonatology. The conformity rate for central venous catheter insertion grew from 42% (September 2008) to 81% (November 2008). Between May 2007 and May 2008, 19 MRSA infections were identified (10 bacteremia, six pneumonia with positive broncho-alveolar lavage, one meningitis, two positive culture of catheters without bacteremia) versus three MRSA infections between June 2008 and May 2009 (two bacteremia, one pneumonia). The decrease in MRSA infection rate was statistically significant. The incidence of nasal MRSA carriage significantly decreased from June 2008. Discussion: The main characteristics of this continuous internal audit were: A direct involvement of all care givers (nurses, doctors, technicians…), A voluntary anonymous report system that permitted to identify 90 points of improvement, A continuous evaluation of the clinical practices by 'quality nurses' and a monthly report to the teams. An associated decrease in MRSA infections rate. Contexte: Des cas groupés d'infections nosocomiales bactériennes (INB) à staphylococcus aureus résistant à la méthicilline (SARM) observés en un an (mai 2007–mai 2008) dans une unité de réanimation néonatale (18 lits) et une unité de néonatologie (31 lits) du même établissement. Objectif principal: Evaluation de la mise en place de mesures de prévention et de leur effet sur le taux d'infections à SARM. Méthode: Un comité de pilotage a été mis en place en mai 2008 (président du CLIN, chef de service, pédiatres et infirmières des unités de soins concernées, cadres de santé, médecins hygiénistes et bactériologistes). Deux groupes opérationnels de 15 personnes chacun ont été créés (1 pour la réanimation néonatale, 1 pour la néonatologie) avec l'objectif de réaliser des séances de formation et d'information du personnel ainsi qu'un audit interne des pratiques de soins. Les équipes soignantes ont été directement impliquées dans le repérage de situations à risque par un système de déclaration anonyme et volontaire. Au cours de la période mai 2008-décembre 2008, les deux groupes opérationnels ont assuré l'analyse des résultats et ont proposé au total 90 actions retenues par le comité de pilotage. Une observation directe des procédures de soins avec recueil systématisé des données a été mise en place dés le mois de mai 2008. Cette observation était assurée par des infirmières spécifiquement formées pour cette activité (2 équivalents temps-pleins). Des réunions mensuelles des groupes opérationnels ont été organisées pour faire le point des pratiques (hygiène des mains, pose et entretien des voies centrales…), analyser les observations d'INB avérées (critères des CDC d'Atlanta) et l'évolution des taux de portage nasal de SARM (à partir de mai 2008). Les conclusions ont été diffusées aux équipes de soins par voie d'affichage. Un audit externe de la méthode a été réalisé en novembre 2008 par l'Institut National de Veille Sanitaire et le CCLIN Est. Résultats: Sur 90 points d'amélioration identifiés, 82 actions ont été menées (90%) de mai à décembre 2008. La consommation de solution hydro-alcoolique a doublé à partir de juin 2008. Entre juillet et décembre 2008, les taux de conformité pour la désinfection des mains sont passés de 85% à 94% en réanimation, et de 38% à 95% en néonatologie. Le taux de conformité des poses des voies centrales est passé de 42% en septembre 2008 à 81% en novembre 2008. Entre mai 2007 et mai 2008, 19 INB à SARM ont été observées (10 bactériémies; 6 pneumopathies confirmées par LBA; 1 méningite; 2 infections sur cathéters centraux sans bactériémie) vs 3 sur la période juin 2008-mai 2009 (2 bactériémies; 1 pneumopathie). La réduction du taux d'INB est significative. L'incidence de la colonisation nasale à SARM a significativement diminué à partir de juin 2008. Discussion, perspectives: Les principales caractéristiques de cette démarche d'auto-évaluation continue ont été: une implication directe de tout le personnel (IDE; médecins; auxiliaires; agents techniques) des unités de soins une déclaration anonyme et volontaire d'évènements précurseurs qui a conduit à identifier 90 points d'amélioration (90% d'application effective). une évaluation en temps réel de l'application des procédures par des infirmières « qualité » avec un retour mensuel d'information aux équipes. une réduction du taux d'INB à SARM associée à ces mesures.